Heart Attack Detection by Heart Beat Sensing - Hussein, Maryam Haidar; Abdalwahab, Abdalwahab Anwer (American Journal of Botany and Bioengineering, 2025)
Nowadays numerous persons are mislaying their life owing to heart attack and shortage of medical attention to patient at correct stage. Hence, in this project we are implementing heart rate monitoring and heart attack recognition system using IoT. The patient will carry hardware having sensors with android application. The heartbeat sensor will allow checking heart beat readings and transmit them over the internet. The user may set the high and low level of heartbeat limits. Once these limits are set the system can start monitoring the patient’s heartbeat and as soon as the heart beat readings goes above or below the limit set by the user the system will send an alert about high or low heartbeat as well about chances of heart attack. Keywords Heart rate sensor, Monitor, Detect, IoT, Android smart phone. Heart attack can occur when the flow of blood to heart is blocked. Owing to late diagnosis of heart attack we are inadequate to save the lives of many humans. In this paper, we suggest a system that will detect heart attack by monitoring the heart rate based on IoT (Internet of Things). For a healthy adult, ordinary heartrate is 60 to 100 bpm (beats per minute). Athlete’s heart beat generally range from 40 to 60 bpm depending upon their fitness. If a person’s heart rate is constantly over 100 beats per minute then the person is said to be having higher heart rate which is also notorious as tachyarrhythmia. It can diminution the efficiency of heart by letdown the amount of blood pumped through the body can result in chest pain and lightheadedness. With the advancement in technology it is easy to monitor the patient’s heart rate even at home. IoT is dexterity of network mechanism to intellect and gather information from world ubiquitously us then share the information athwart internet anywhere it can be managed for some tenacity.